Effect of Anion-Conducting Electrolytes in Pore-Filling Membranes on Performance and Durability in Water Electrolysis - Dahye Jeong; Jin-Soo Park (Membranes)
This study examines the effect of the structural characteristics of anion-conducting monomers within pore-filling anion exchange membranes on the performance and durability of anion exchange membrane water electrolysis. Analysis reveals that acrylamide- and acrylate-based membranes show optimal performance without methyl groups, with acrylamide-based membranes outperforming their acrylate counterparts in current density, particularly at 1.8 V. The AC-AA and AC-MAA monomers demonstrate durability, with AC-MAA showing enhanced alkaline stability, likely due to the presence of a methyl group, resulting in an increase rate of 746.6 μV/h compared to AC-AA’s 1150 μV/h. This study also shows that a commercial membrane exhibits a decrease rate of 3116 μV/h, underscoring the pore-filling membrane’s superior durability. Furthermore, the findings highlight that pore-filling membrane technology enables better durability and performance in electrolysis environments compared to the commercial homogeneous membrane, particularly when alkaline conditions are present. This research provides a foundation for designing high-performance, durable membranes for efficient hydrogen production, particularly under water electrolysis conditions.